Health Impacts and Post-Flood Handling in Ijen District, Bondowoso Regency - Meri Dwi Apriliyanti; Hadi Prayitno; Isa Ma’rufi (Humanistic Network for Science and Technology (HNST), 2022)
Bondowoso Regency is ranked 19 out of 29 regencies in East Java based on the mapping of disaster-prone areas. Rampant land clearing in Ijen District has resulted in flooding. The results of the preliminary study affected by the flood reached 503 people. The five most non-traumatic health problems are myalgia, hypertension, shortness of breath, gastritis and conjunctivitis. This study used a quantitative approach, the type of analytical research with a cross-sectional research design. The research was conducted in Sempol Village and Kalisat Village, carried out in August 2021. The population of this study was 101 respondents. The research sample was 81 respondents in 4 hamlets located in Ijen District and five respondents from the health task force, surveillance officers, BPBD officers, Sempol and Kalisat village nurses. The sampling technique used was proportional sampling. The variables studied included flood disasters, flood disaster management, health impacts including myalgic, hypertension, shortness of breath, gastritis, conjunctivitis. Collecting data using questionnaires and interviews. Data analysis with logistic regression test and partial least square. The results showed that there was no effect of flooding on the incidence of myalgic, hypertension, shortness of breath, gastritis and conjunctivitis caused by other factors such as psychological stress, excessive activity, and personal hygiene. Post-disaster management strategies were classified as good, policies related to mitigation were available and appropriate, community response and community cohesiveness in disaster management were classified as good. Keywords: flood disaster; management; health impacts